2017
DOI: 10.1111/apt.14153
|View full text |Cite
|
Sign up to set email alerts
|

The use of selective serotonin receptor inhibitors (SSRIs) is not associated with increased risk of endoscopy‐refractory bleeding, rebleeding or mortality in peptic ulcer bleeding

Abstract: According to our data, treatment with SSRIs does not influence the risk of endoscopy-refractory bleeding, rebleeding or 30-day mortality in peptic ulcer bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
0
20
1
Order By: Relevance
“…Evidence for blood transfusion (one study [ 54 ]), endoscopy-refractory bleeding (one study [ 55 ]), and rebleeding (one study [ 55 ]) are inconclusive owing to the limited data available ( Supplementary, eTable 8 ). However, no study has reported bleeding complications in terms of bleeding related to mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for blood transfusion (one study [ 54 ]), endoscopy-refractory bleeding (one study [ 55 ]), and rebleeding (one study [ 55 ]) are inconclusive owing to the limited data available ( Supplementary, eTable 8 ). However, no study has reported bleeding complications in terms of bleeding related to mortality.…”
Section: Resultsmentioning
confidence: 99%
“…The use of selective serotonin reuptake inhibitors has been associated with a modest increase in the risk of NSAID‐induced gastroduodenal bleeding . However, a recent study did not show an increased risk of bleeding in either patients with selective serotonin reuptake inhibitor intake or in patients with a combination of selective serotonin reuptake inhibitors and NSAID intake . With the exception of one Danish study showing that H. pylori infection increases the overall risk of serious upper gastrointestinal bleeding in patients using selective serotonin reuptake inhibitors with an adjusted OR of 2.73 (95% CI = 1.17‐6.36), no other data are available on this topic .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Laursen et al found that SSRI was not associated with increased risk of endoscopy‐refractory peptic ulcer bleeding. The discrepancy may be accounted by the use of different primary outcomes that endoscopy‐refractory bleeding was used in the study by Laursen et al, which is the most severe end of the bleeding spectrum.…”
Section: Discussionmentioning
confidence: 89%